The moral disarmament of France : education, pacifism, and patriotism, 1914 - 1940 - Siegel, Mona L. 1996- (Studies in the social and cultural history of modern warfare;, 2004)
In 'The Moral Disarmament of France' Mona Siegel explores the widespread pacifism amongst school teachers in France between the wars, & argues that while they stripped their classrooms of militarist symbols, their teaching remained firmly rooted in patriotic & republican traditions.